The Implementation of Evaluation and Assessment of Language Learning in Merdeka curriculum at Vocational Schools - Fernando De Napoli Marpaung; Donny Adiatmana Ginting; Muhammad Hasan; Rosmen (LPPM STKIP AL MAKSUM, 2023)
This research aims to explore the implementation of language learning evaluation and assessment in the Independent Curriculum at Al Maksum Vocational High School (SMK), especially in language subjects. The data collection method involves observation and interviews, with a focus on the evaluation model used, assessment methods, and the obstacles teachers face in the evaluation and assessment process. The results of interviews with six language teachers showed variations in evaluation forms, such as written tests, presentations, group discussions, and projects. The main obstacles faced include time constraints, lack of training, and technological barriers during online learning. As innovations, the use of technology in assessment, project-based learning, and adaptive learning are proposed to increase the effectiveness of evaluation and assessment. This research contributes to understanding the dynamics of evaluation and assessment in language learning in the context of an independent curriculum, with implications for improving the quality of learning at Al Maksum Vocational School.